Perbedaan Nadi Kerja Dan Tekanan Darah Pada Karyawan Terpapar Intensitas Kebisingan Di Atas Dan Di Bawah Nilai Ambang Batas (NAB) Pada Bagian Produksi Di Pt. Iskandar Indah Printing Textile Surakarta - TUNGGAL DEWI, DINASTI, Tarwaka, PGDip, Sc, M.Eng (2016)
Noise not only can cause hearing loss but through hormonal mechanisms may increase frequency pulse and blood pressure. The purpose of this study was to determine differences in working pulse and blood pressure in employees exposed to noise intensity above and below the threshold limit value on the production of PT. Iskandar Indah Textile Surakarta. This research method using observational design with cross-sectional approach. The study population was employees of the weaving as many as 40 employees, part of printing as many as 20 employees, and part riching many as 20 employees. Selection of the sample with purposive sampling method as many as 26 employees of the weaving, and 13 employees of the printing and 13 employees of the riching. The statistical test working pulse and blood pressure using the Mann Whitney-U by. The results showed that there is a difference on working pulse on employees exposed to noise intensity above and below the threshold limit value on the production of PT. Iskandar Indah Textile Surakarta with significant a p-value = .000 or p-value = ≤0.05 and there is a difference in blood pressure on employees exposed to noise intensity above and below the threshold limit value on the production of PT. Iskandar Indah Textile Surakarta with significant a p-value = .005 or p-value = ≤0.05. Based on this study, the use of standard ear protection can prevent the increase in pulse rate and blood pressure.